P-008 Pulsatile tinnitus and subclinical idiopathic intracranial hypertension. An evaluation on MRI signs. (23rd July 2022) - Rustici, A; Cancelliere, N; Vanek, I; Marotta, T; Spears, J; Mendes Pereira, V
Abstract : Purpose: To investigate the prevalence of intracranial and ophthalmological signs of Intracranial Hypertension (IH) on MRI in patients with Pulsatile Tinnitus (PT). Materials and Methods: We included all patients assessed with PT in our center. We included in the study all patients with PT who underwent MRI between January 2020 and December 2021. Both treated and untreated patients were considered and, in the case of treatment only pre-treatment MRIs were evaluated. We evaluated imaging and undiagnosed ophthalmological signs of intracranial hypertension. Exclusion criteria included non-pulsatile tinnitus and primary diagnosis of IIH or venous thrombosis. Results: We included four-hundred-fifteen patients in our study. MRI imaging was evaluated for IIH signs and we also included neuroophthalmological assessment if present. Our preliminary results on 20% of the patients demonstrate a high prevalence of both intracranial and ocular MRI signs of IIH in patients with isolated PT. Our analysis from MRI imaging of patients with PT as primary diagnosis showed: 38.5% of patients presented with a partial empty sella, 38.5% of caudal ectopy of cerebellar tonsils into foramen magnum, 36.9% of slit-like appearance of the lateral ventricles and 32.3% a bilateral Meckel's cave enlargement. There were 64.6% of patients who presented with bilateral Optic Nerve Sheath Distension, 49.2% presented with bilateral Optic Nerve vertical Tortuosity and posterior globe flattening, while 40% presented Optic Nerve Head protrusion. Conclusion: This study demonstrates a high prevalence of IIH signs in patients presenting with PT, suggesting the possibility of initial signs of intracranial hypertension probably related to venous outflow impairment. A neuro-ophthalmological assessment could be considered for this subgroup of PT patients with signs of IH. Disclosures: A. Rustici: None. N. Cancelliere: None. I. Vanek: None. T. Marotta: None. J. Spears: None. V. Mendes Pereira: None.